Physical Therapists as Partners for Community Fall Risk Screenings and Referrals to Community Programs - Jennifer L. Vincenzo; Colleen Hergott; Lori Schrodt; Subashan Perera; Jennifer Tripken; Tiffany E. Shubert; Jennifer S. Brach (Frontiers Media S.A., 2021)
Objectives: Physical therapists (PTs) are integral team members in fall prevention in clinical settings; however, few studies have investigated PTs' engagement in pro-bono community-based falls prevention. Therefore, we aimed to describe the characteristics of PTs and physical therapist assistants (PTAs) in the United States who conduct community-based fall screenings, the reach of screenings, their knowledge and utilization of the Centers for Disease Control and Prevention's fall-risk screening toolkit (STEADI, Stopping Elderly Accidents, Deaths, and Injuries), and therapists' knowledge and referrals to evidence-based programs (EBPs) and community resources.Methods: A cross-sectional survey distributed to a convenience sample of PTs/PTAs in the United States through news-blasts, and social media.Results: Four hundred and forty-four therapists who worked with older adults completed the survey. Approximately 40% of the respondents (n = 180) conduct screenings, most frequently annually. People who screen tend to be PTs with >20 years of experience, work in outpatient/wellness or academia, and be involved in the least amount of direct patient care. The majority (n = 344, 77.5%) of survey respondents were somewhat to very familiar with the STEADI, and ~84% (n = 114) of respondents who were very familiar with the STEADI (n = 136) use the toolkit to conduct community-based, pro-bono fall risk screenings. Twenty-six percent (n = 14) out of the 53 PTAs who responded to the survey conduct falls screenings in the community. Of the PTs/PTAs who conduct community-based fall screenings (n = 180), ~ 75% (n = 136) are aware of and refer older adults to EBPs. Over half also refer to Silver Sneakers and/or senior centers.Discussion: PTs and PTAs are key partners in evidence-based multifactorial fall prevention in the community. Data helps inform community organizations that most PTs who engage in community-based fall risk screening utilize the STEADI toolkit and refer to community-based programs. Community organizations seeking PT partners to engage in fall risk screenings and promote referrals to local resources or EBPs will likely have the most success collaborating with local physical therapy education programs or physical therapy clinic managers.